Development and validation of the regarding infection prevention and control among environmental service workers on knowledge, attitudes, practise, and experience questionnaire - Chen, Xiaohang; Zhang, Pan; Zhang, Ruhan; Li, Shuting; Cao, Rui; Hu, Fen; Jin, Ying-Hui; Lin, Likai; Cai, Lin; Feng, Bilong; Zhang, Chunhua; Wang, Xinghuan (Frontiers in Public Health, 2023)
Purpose: This study aimed to develop and test the validity and reliability of the Knowledge, Attitudes, Practice, and Experience regarding Infection Prevention and Control-associated Questionnaire for Environmental service workers. Design: This study was a development and validation study of a questionnaire using multiple methods, including literature review, questionnaire survey, and Delphi technique. Methods: Phase I of the study entailed the development of items through an extensive literature review and two round Delphi process with 15 experts specialized in infection prevention and control, environmental service worker management, or scale construction to examine the content validity of the questionnaire. Phase II involved administering the questionnaire to a convenience sample of 1176 environmental service workers from the public hospital from 13 provinces in China to evaluate its construct validity and reliability. Findings: In the two rounds of Delphi consultation, the recovery rate were 93.75% and 100%. Moreover, the expert authority coefficient was 0.93, and the coordination coefficients of expert opinions in the first round were as follows: correlation of 0.204 and importance of 0.249 for the first-level index; correlation of 0.128 and importance of 0.142 for the secondary index. In round two, the coordination coefficients of expert opinions were as follows: correlation of 0.221 and importance of 0.221 for the first-level indicators; correlation of 0.096 and importance of 0.101 for the secondary index. The results for the index were P < 0.05 for the two rounds. The pilot survey shows the instrument was excellent content validity (S-CVI/Ave = 0.989). The overall internal consistency was excellent (Cronbach’s α = 0.967). The questionnaire ultimately comprised four first-level indices (knowledge, attitudes, practice, and experience) and 49 second-level indices. Conclusion: The Questionnaire demonstrated good reliability and validity and is effective in measuring levels of infection prevention and control-related knowledge, attitudes, practice, and experience among environmental service workers. It will provide a tool for future national investigations of the current infection prevention and control situation among environmental service workers. Future research should explore determinants of environmental service workers’ knowledge, attitudes, practice, and experience and associations between infection prevention and control knowledge, attitudes, practices, and experience.